1960
DOI: 10.1111/j.2044-8279.1960.tb01665.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Conservation of Substance in the Junior School Child

Abstract: Almost all the children in a Junior school were tested individually,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1961
1961
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Lovell (1959) confirmed Piaget's developmental stages, but Lovell and Ogilvie (1960) found, contrary to Piaget, that substance is not conserved for all time upon attainment, but is conserved only in very specific kinds of situations at first and then expands to others with experience and matura-tion. Lovell andOgilvie (1960, 1961) also pointed out clearly the problems of interpreting what children mean or understand in conversation.…”
Section: Mathematical and Physical Conceptsmentioning
confidence: 70%
“…Lovell (1959) confirmed Piaget's developmental stages, but Lovell and Ogilvie (1960) found, contrary to Piaget, that substance is not conserved for all time upon attainment, but is conserved only in very specific kinds of situations at first and then expands to others with experience and matura-tion. Lovell andOgilvie (1960, 1961) also pointed out clearly the problems of interpreting what children mean or understand in conversation.…”
Section: Mathematical and Physical Conceptsmentioning
confidence: 70%
“…Piaget's findings which have been supported by several studies (Dodwell, 1968;Elkind, a, b, c, 1964Kofsky, 1968;Lovell, Mitchell, & Everett, 1962;Lovell & Ogilvie, 1960Uzgiris, 1964;Wohlwill, 1960) indicate that conservation of substance develops first followed by conservation of weight and then volume. Furthermore, many of the training studies have shown that while there has been some success with certain training procedures designed to help a child understand a particular conservation task, there is mixed evidence with respect to whether or not transfer of learning occurs.…”
mentioning
confidence: 74%
“…A sample of the best-known experiments on the concept of conservation of quantity might include publications by Beard (1963), Lovell and Ogilvie (1960), Smedslund (1961), Elkind (1961), and Uzgiris (1964). We shall look at some of the results reported by these authors and then describe an experiment of our own designed to discover whether one of the extraneous factors which might affect the results of a test might be the degree to which the pupil is allowed actively to manipulate the materials involved in that test.…”
Section: Difficulties Of Using Piagetian Tests In the Classroom--i Kmentioning
confidence: 95%